Low dose of aPCC after the initial treatment in acquired haemophilia A is useful to reduce bleeding relapses: Data from the FAIR registry. Issue 174 (February 2019) - Zanon, E.; Pasca, S.; Siragusa, S.; Napolitano, M.; Santoro, C.; Mameli, L.; Rocino, A.; ,
Abstract: Background: Bypassing agents are the first line therapy in patients with acquired haemophilia A (AHA). Activated prothrombin complex concentrate (aPCC) proved to be effective as initial treatment, but 20% of patients (pts) had relapses. aPCC as short-term prophylaxis to reduce subsequent bleeds is still not clear. Aim: To evaluate whether a short-term prophylaxis with low dose of aPCC can reduce bleeding relapses after initial AHA treatment, maintaining safety. Methods: The FAIR Registry is a retrospective-prospective study started on December 2012, that collected data on all pts with AHA treated with aPCC in 12 Italian Haemophilia Centers. All statistical analyses were carried out in the 56 pts included in the registry. Results: 31 retrospective and 25 prospective pts were evaluated.101 bleeds requiring treatment were reported, 84.1% spontaneous, 71.3% involving muscles or skin. Major bleeds were 38, 6%. Low-dose aPCC as short-term prophylaxis was started after the first resolved episode in 15/56 pts, 58% of whom prospective, in a mean dose of 54.2 ± 23.0 IU/kg, higher (61.4 ± 23.4 IU/kg) in the prospective group than in the retrospective one (44.3 ± 19.7 IU/kg) and it was continued up to a mean of 20.5 ± 17.6 days, similar in both groups. A total of 32 bleeding relapses were reported, 87.5% in the retrospective group. Only 9.4% occurred during short-term prophylaxis ( p < 0.05). In our Registry no thromboembolic events were found. Conclusion: Initial AHA treatment with aPCC proved to be highly effective, but a consecutive low dose as short-term prophylaxis seems to demonstrate a significant reduction in bleeding relapses maintaining safety.